State and Dynamics of Development of the Russian Leasing Market (Brief Statistical Analysis) - L. Yu. Arkhangel’skaya (Учёт. Анализ. Аудит)
The study subject of the paper is the directions of development of leasing in Russia in various forms of its manifestation. There is no generally accepted classification of types of leasing today — the system of statistical indicators characterizing the state and development of the financial leasing market is in a state of formation; the factors (external and internal) and cause-and-effect relationships that bring such an uneven development of the leasing services market in a way of changing the legal environment, new challenges of the time (economic, financial, social) have been little studied. Thereby, the study of leasing as a unique tool for investing in assets (including labor force) in various spheres of human activity is a relevant scientific and the applied problem. Within the framework of this paper, being used statistical methods for analyzing the structure and dynamics of the phenomena of public life, the features and trends that are emerging in thebRussian market of leasing services are investigated, a forecast for 2020 is being constructed. and expert agencies and summarizes the results of the comprehensive statistical analysis of one of the segments of the financial intermediation services market. The proposed methodology for analyzing a segment of the financial intermediation services market using the example of leasing can be widely used in the analytical activities of expert agencies, financial analysts, be useful in scientific and applied research conducted by research organizations and universities, as well as in the training of scientific and pedagogical personnel in financial and economic profile universities.